Comparative study on microencapsulated of natural and waste sunflower oil as self-healing agent - BAHAROM, Zulkhibri; IDRIS, Maizlinda Izwana; Lee, Te Chuan; ABDULLAH, Hasan Zuhudi (2020)
Microencapsulation of natural vegetable oil as a self-healing agent on metal coating became demanded lately. This paper underlines the microcapsule containing natural and wastes sunflower oil as a self-healing agent that was fabricated for the backbone of corrosion coatings. The results in this paper indicated the distinguished potential of waste sunflower oil as compared to natural sunflower oil. The diameter of microcapsules synthesized from natural sunflower oil and waste sunflower oil both in range of 3-4 µm. The shell of microcapsules microencapsulated from natural sunflower oil showed rough micro-structure while the shell of microcapsules microencapsulated from waste sunflower oil showed smooth micro-structure. The main parameter studied in this research was the varient of stirring speed during the process of microencapsulation. The involvement of stirring speed starts from 200 to 400 rpm. The microcapsules undergo varient of stirring speed analyzed on the yield and core content of microcapsules. The microcapsules from natural produced 29-50 % while waste resources bring 26-48 % of yield productions. The core content of microencapsulated natural sunflower oil generates 55-64 % core content as comparing with waste sources which produce 56-67 % of core content. It can be concluded that it was proved that sunflower oil could be considered as an alternative resource for self-healing agent in metal coating either encapsulated from natural or waste raw materials. The incorporation of green and natural material as a self-healing agent significantly influences the sustaining the environment to the safest stage.